2011
DOI: 10.1186/ar3220
|View full text |Cite
|
Sign up to set email alerts
|

Salivary glands of primary Sjögren's syndrome patients express factors vital for plasma cell survival

Abstract: IntroductionThe presence of circulating Ro/SSA and La/SSB autoantibodies has become an important marker in the classification criteria for primary Sjögren's syndrome (pSS). Plasma cells producing these autoantibodies are mainly high affinity plasma cells originating from germinal centre reactions. When exposed to the right microenvironment these autoimmune plasma cells become long-lived and resistant to immunosuppressive treatment. Since autoimmune plasma cells have been detected in the salivary glands of SS p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
86
3
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 116 publications
(98 citation statements)
references
References 54 publications
8
86
3
1
Order By: Relevance
“…In agreement with the latter studies, we demonstrated here using both cell surface immunophenotyping and gene expression analyses that B cell differentiation did not progress beyond the follicular stage in lacrimal glands from NOD mice, with no signs of GC or plasma cell differentiation markers and gene expression during disease progression. This observation contrasts with what was reported in the glands from pSS patients which show GC formation in 10 to 30% of the cases and striking accumulation of plasma cells with a long-lived phenotype within the target tissue [3][4][5].…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…In agreement with the latter studies, we demonstrated here using both cell surface immunophenotyping and gene expression analyses that B cell differentiation did not progress beyond the follicular stage in lacrimal glands from NOD mice, with no signs of GC or plasma cell differentiation markers and gene expression during disease progression. This observation contrasts with what was reported in the glands from pSS patients which show GC formation in 10 to 30% of the cases and striking accumulation of plasma cells with a long-lived phenotype within the target tissue [3][4][5].…”
Section: Discussioncontrasting
confidence: 99%
“…Despite being the second most common rheumatic disease after rheumatoid arthritis, no disease-modifying drug is currently available to treat pSS patients. The histological hallmark of the disease is a multifocal nodular immune infiltration of the exocrine glands, predominantly composed of CD4 + T and B lymphocytes, but also CD8 + T cells and long-lived plasma cells [2][3][4]. In addition, ectopic germinal center (GC)-like structures were observed in 10 to 30% of patients [2,5]; their presence was associated with autoantibody seropositivity, disease activity, and higher risk of developing lymphoma [2,[5][6][7].…”
Section: Introductionmentioning
confidence: 99%
“…The angiogenic effects of VEGF-A may be responsible for the increased number of blood vessels observed in SS salivary glands. 22,23 The enhanced angiogenesis was associated with an increased VEGF-A/VEGFR2 signaling, as demonstrated by the observation of an increased amount of phosphorylated VEGFR2 in SS salivary glands biopsies. Given the critical role of VEGFR2 signaling in angiogenesis, antiRo/SSA Abs-regulated VEGFR2 activation may represent an important mechanism in the control of angiogenesis in SS.…”
Section: Tace Is Involved In Vegf-a-dependent Angiogenesis Induced Bymentioning
confidence: 95%
“…However, the role of CD28 might be controversial, as Njau et al (11) reported increased Ig titers and PC numbers in CD28 2/2 chimeras. Whereas the large majority of MPCs are localized in the bone marrow (5,12), LLPCs are also found in lymphatic organs such as spleen (13), lymph nodes (14), mucosa-associated lymphatic tissues (15), as well as in chronically inflamed tissues such as the synovium in rheumatoid arthritis (16), the CNS in induced multiples sclerosis (17), the kidneys in systemic lupus erythematosus (SLE) (18), the salivary glands in Sjögren's syndrome (19), or the lung during chronic airway inflammation in allergy/asthma (20,21). In secondary lymphatic tissues, PCs reside in extrafollicular areas such as the lamina propria of mucosa and the red pulp of spleen, and LLPCs are associated with APRIL, BAFF, and IL-6 sources in the vicinity (14,15,22,23).…”
mentioning
confidence: 99%